The Ownership Structure of Repurchasing Firms - Johannes A. Skjeltorp; Bernt Arne Ødegaard (Norges Bank, 2004)
This paper provides an examination of the ownership structure in Norwegian firms that announced repurchase plans during the period 1999 through 2001, as well as for groups of these firms conditional on whether they actually executed repurchases or not. By using detailed information on various ownership variables that can be related to corporate governance mechanisms, the paper also examines whether the propensity for firms to announce a repurchase program depends on the ownership composition. Some interesting patterns are found which are consistent with models where firms with potentially the highest agency problems use repurchases to mitigate agency costs. However, a high insider ownership in these firms may also suggest that asymmetric information, shareholder expropriation and entrenchment may also be motivations for why firms repurchase shares.
hdl:11250/2498546
Keywords: G10; G32; G35; 330; stock repurchases; ownership structure; corporate governance